Harvesting Baltic Microalgae Chlorella vulgaris BA-167 Using Coagulant Flokor 1.2A via Static Sedimentation Under Auto- and Targeted Flocculation - Małgorzata Płaczek; Agnieszka Błasiak; Stanisław Witczak (Applied Sciences, 2025)
High dewatering costs, resulting from the harvesting and separation of microalgae from the cultivation medium, pose a significant challenge to the large-scale commercial production of algae-based products, accounting for 20–60% of total cultivation expenses. This study presents research findings on the recovery of Baltic green microalgae Chlorella vulgaris BA-167 from water under static sedimentation conditions, evaluating its potential as a cost-effective harvesting method. The study investigates the effect of suspension concentration on the kinetics and efficiency of sedimentation under both autoflocculation and targeted flocculation conditions, using the Flokor 1.2A coagulant, which is commonly employed in industrial water treatment processes in Poland. The novelty of this research lies in the application of the new coagulant Flokor 1.2A to explore its potential for harvesting Chlorella vulgaris BA-167 cultivated under laboratory conditions. The results demonstrate a strong correlation between the algae removal rate and their initial concentration in the suspension, within the range of 0.375–2.380 g/L. Under autoflocculation conditions, the final minimum algae concentration in the liquid after sedimentation ranged from 0.078 to 0.148 g/L, corresponding to initial concentrations of 0.960 g/L and 0.615 g/L, respectively. Experimental results indicate that combining sedimentation with targeted flocculation significantly increases microalgae harvesting efficiency. Flokor 1.2A facilitates the coagulation and agglomeration of microalgae cells, promoting the formation of larger aggregates (flocs) ranging from 20 μm to 690 μm, which settle more easily during gravity-driven sedimentation. Within the coagulant concentration range (CF) of 0.01–0.36 g/L, sedimentation time was reduced by 3–7 times, and algae harvesting efficiency exceeded 92%. The greatest reductions in algae concentration occurred with 0.12 g/L of coagulant for 0.615 g/L algae and 0.17 g/L for 0.960 g/L algae, achieving maximum harvesting efficiencies of 83.2% and 92.9%, respectively. These results represent a 2.02–2.53-fold improvement over autoflocculation.